Le travail des femmes a une histoire: l`industrialisation - Lévesque, Andrée (Chroniques féministes, 1996)
Keywords: Femmes; Travail

La syndicalisation des femmes dans l'industrie montréalaise du vêtement, 1936-1937 - Gagnon, Gemma (Université du Québec à Montréal, 1990)
Keywords: Confection; Femmes; Grèves; Union internationale des ouvriers du vêtement pour dames; Vêtements

La structure spatiale des déplacements pendulaires des femmes et des hommes dans la région de Montréal - Lemelin, André; Gatignol, Agnès (Cahiers de géographie du Québec, 1999)

Quand les ménagères se font militantes: la Ligue auxiliaire de l'Association internationale des machinistes, 1905-1980 - Murray, Sylvie (Labour / Le travail, 1992)
Keywords: Femmes

Nouvelles dynamiques métropolitaines et stratégies spatiales de la main-d'oeuvre: le cas d'employées de bureau montréalaises - Chicoine, Nathalie (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Femmes; Travail

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

'Ruffled' Mistresses and 'Discontented' Maids: Respectability and the Case of Domestic Service, 1880-1914 - Fahrni, Magda (Labour / Le travail, 1997)
Keywords: Domestiques; Femmes

La crise ordinaire: les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Labour / Le travail, 1992)
Keywords: Crise; Famille; Femmes

Travail domestique et crise économique. Les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Université de Montréal, 1990)
Keywords: Crise; Famille; Femmes

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

Trabajo Asalariado, género e identidad: la inserción de las Mujeres Colombianas en Montreal - Osorio Ramírez, Amantina Maria (Université de Montréal, 1996)
Keywords: Colombiens; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Sweated Labour: Female Needleworkers in Industrializing Canada - McIntosh, Robert (Labour / Le travail, 1993)
Keywords: Confection; Femmes; Travail

Couples en emploi et morphologie sociale des quartiers de Montréal, 1971-1991 - Villeneuve, Paul (Sociologie et sociétés, 1995)
Keywords: Femmes; Quartiers; Travail

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
Keywords: Enfants; Famille; Femmes

Les infirmières de la Métropolitaine au service des Montréalaises - Baillargeon, Denyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Assurance; Femmes; Infirmières

Hello, Central? Gender, Technology and Culture in the Formation of Telephone Systems - Martin, Michèle (McGill-Queen's University Press, 1991)
Keywords: Bell Canada; Femmes; Téléphone

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

The Promise: Communist Organizing in the Needle Trades, the Dressmakers' Campaign, 1928-1937 - Steedman, Mercedes (Labour / Le travail, 1994)
Keywords: Communistes; Confection; Femmes; Travail

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Keywords: Africains; Femmes; Infirmières; Noirs

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Entre l'accès à l'égalité et la préservation des modèles: ambivalence du discours et des revendications du Comité féminin de la CTCC-CSN, 1952-1966 - Piché, Lucie (Labour / Le travail, 1992)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Femmes; Féminisme; Travail